Optimization of global gravitational potential models with detailed gravity anomalies in Southern VietnamOptimization of global gravitational potential models with detailed gravity anomalies in Southern Vietnam - Phung Trung Thanh (Journal of Forestry Science and Technology, 2024)
This study evaluates the accuracy of several global gravity field models, specifically EGM 2008, EICGEN-6C4, SGG-UGM-1, SGG-UGM-2, and GECO, using detailed gravity anomaly data from 1968 points in the southern plains of Vietnam. The evaluation process followed a rigorous methodology to ensure precision. Results indicate that these models exhibit similar accuracy levels in the experimental area, with a mean error of approximately 6.2 mGal. Among them, The SGG-UGM-2 model, demonstrated the highest precision, with a fluctuation range of -29.2425 to +74.9010 mGal. These newer generation models, which incorporate additional satellite data, offer enhanced reliability compared to the EGM2008 model. The fluctuation ranges for other models also varied: EGM 2008 from -29.8662 to +82.2140 mGal, EIGEN-6C4 from -28.3626 to +74.2292 mGal, SGG-UGM-1 from -28.9500 to +75.5315 mGal, and GECO from -30.5641 to +73.6775 mGal. This research highlights the critical importance of accurate gravity field models for various applications, including geodesy, geophysics, natural disaster management, resource exploration, and military operations. The methodologies employed for accuracy assessment are adaptable to other regions with similar datasets, underscoring the significance of precise geophysical measurements in Vietnam's diverse geographic landscape. The findings support the essential role of gravity anomaly data in understanding Earth's physical properties and emphasize the need for continued evaluation across different regions in Vietnam to establish comprehensive applicability. This research paves the way for advanced studies and practical applications, contributing to a deeper understanding of Earth's physical properties.